Água de reuso e seu efeito sobre parâmetros fisiológicos em manjericão (Ocimum basilicum L.) - Bressan, Dayanne Fabrício [UNESP] (2015)
The water used for irrigation becomes increasingly restricted, making it necessary to try alternative sources of water in case of shortage in agriculture. One effective alternative is the reuse of treated wastewater, especially in regions where the shortage and misdistribution of water make limiting factors to its use. In the global agricultural sector, the use of wastewater for irrigation of plants has been important economically, agronomically and environmentally. The reuse of water is known as low quality, due to high and potentially phytotoxic elements, and concentrations of salt, however, most of this water is rich in mineral elements, which are essential for the development of the vegetable. When used for agricultural purposes, it can bring economic benefits, nevertheless, the effect that these elements can cause in the growth of plants will depend on the water treatment, its origin and the tolerance of species to be studied. Thus, the nutritional, osmotic or saline effects, derived from wastewater on the biochemical and physiological response in Ocimum basilicum L. were analyzed in this current study. For planting, cv. Genovese seeds were used. This cultivar is known as broad leaf basil, which has great commercial and medicinal interests for its essential oil production. The applied treatments were: T1 deionized water; T2 deionized water with NaCl (15 mM); T3 wastewater drawn from the ETE - SABESP, afterwards ozonized, and T4 deionized water with NaCl (30 mM), the treatments were applied via dripping at different sampling times. The parameters of water relations, biometric, gas exchange and IRC relations were not affected by irrigation with wastewater, unlike the saline treatments that reduced water potential, MSF and MST. The biochemical analysis indicated that only the saline treatments activated enzymes related to antioxidant response system. Plants irrigated with wastewater and ...